Multi-colour pulses from seeded free-electron-lasers: Towards the development of non-linear core-level coherent spectroscopies - Bencivenga, Filippo; Capotondi, Flavio; Casolari, Francesco; Dallari, Francesco; Danailov, Miltcho B.; De Ninno, Giovanni; Fausti, Daniele; Kiskinova, Maya; Manfredda, Michele; Masciovecchio, Claudio; Pedersoli, Emanuele (Faraday Discussions, 2014)
We report on new opportunities for ultrafast science thanks to the use of two-colour extreme ultraviolet (XUV) pulses at the FERMI free electron laser (FEL) facility. The two pulses have been employed to carry out a pioneering FEL-pump/FEL-probe diffraction experiment using a Ti target and tuning the FEL pulses to the M2/3-edge in order to explore the dependence of the dielectric constant on the excitation fluence. The future impact that the use of such a two-colour FEL emission will have on the development of ultrafast wave-mixing methods in the XUV/soft X-ray range is addressed and discussed.
CRIS-Team Scopus Importer:2022-07-20